2004
DOI: 10.1021/jp047134+
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of Gold Nanoparticles Produced by Laser Ablation in Aqueous Media

Abstract: The femtosecond laser ablation of a gold target in aqueous solutions has been used to produce colloidal Au nanoparticles with controlled surface chemistry. A detailed chemical analysis showed that the nanoparticles formed were partially oxidized by the oxygen present in solution. The hydroxylation of these Au-O compounds, followed by a proton loss to give surface Au-O -, resulted in the negative charging of the nanoparticles. The partial oxidation of the gold nanoparticle surface enhances its chemical reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
552
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 612 publications
(604 citation statements)
references
References 51 publications
48
552
4
Order By: Relevance
“…rsif.royalsocietypublishing.org J. R. Soc. Interface 11: 20130931 measurements verified the presence of Au-O bonds on the surface [103]. An indirect verification of a pI value in ligand-free noble metal systems was recently found for Au 50 Pt 50 -alloy NPs which were laser-ablated at different pHs.…”
Section: Ph Effectsmentioning
confidence: 67%
See 2 more Smart Citations
“…rsif.royalsocietypublishing.org J. R. Soc. Interface 11: 20130931 measurements verified the presence of Au-O bonds on the surface [103]. An indirect verification of a pI value in ligand-free noble metal systems was recently found for Au 50 Pt 50 -alloy NPs which were laser-ablated at different pHs.…”
Section: Ph Effectsmentioning
confidence: 67%
“…Specific accumulation of chaotropic anions in the nanoenvironment of NPs does not only affect colloidal stability, it also interferes with the growth mechanism of ligand-free NPs. As a result, these ions induce a size quenching effect during NP growth which was reported for gold [31,97,103] and silver NPs [102,[104][105][106]. This means that in a micromolar concentration regime increasing ionic strengths significantly reduce NP size and their NP size distribution.…”
Section: Ion Effectsmentioning
confidence: 71%
See 1 more Smart Citation
“…Pulsed laser ablation in liquids (PLAL) is a recently emerged alternative single step approach enabling sizecontrolled generation of stable nanoparticle colloids [7][8][9][10] with outstanding purity and novel surface chemistry not reproducible by any other conventional manufacturing route. Recently, Sylvestre et al revealed the presence of the oxidation states Au + and Au 3+ besides the metallic Au 0 due to partial oxidation of the nanoparticles in aqueous media [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sylvestre et al revealed the presence of the oxidation states Au + and Au 3+ besides the metallic Au 0 due to partial oxidation of the nanoparticles in aqueous media [9]. Owing to this partial oxidation, laser-generated gold nanoparticles act as electron acceptors; hence, they are easily coordinated by molecules bearing electron donor moieties as thiol, amine or carboxyl groups added to ablation media prior (in-situ conjugation) or after (ex-situ conjugation) the laser process.…”
Section: Introductionmentioning
confidence: 99%